Increasing Literature Capabilities in Early Childhood with Learning Through Youtube Social Media and Whats’App Groups - Suryatini, Lilis (International Proceedings of Nusantara Raya, 2022)
Early Childhood Education is an important period and very influential on the process of child development. At the age of 0-6 years, the development of children's abilities enters the golden age, this is because at this age the absorption and ability of children is very high, curiosity is large enough to encourage children to do various activities that can give them meaningful experience. and meaningful. This study aims to determine the description of improving early childhood literacy skills by learning through social media Youtube and WhatsApp groups. The method used in this research is descriptive qualitative. One of the problems in learning in early childhood is limited learning time at schools and less varied learning media, which results in less than optimal literacy in early childhood. Learning through social media YouTube and WhatsApp groups by means of teachers making or selecting videos. learning videos that are in accordance with the material on youtube are then watched together in class and the Youtube link is shared through the student's parents WhatsApp group then with the guidance of the children's parents watch youtube learning materials given at school. The results of research conducted at PAUD Cempaka III, Dawuhanwetan village, Kedungbanteng sub-district, showed that by learning through YouTube social media and WhatsApp groups, early childhood literacy skills have increased, through YouTube videos, children can watch material repeatedly, this certainly makes it easier for them to learn. understand the material at home.